2004
DOI: 10.1002/ar.a.20069
|View full text |Cite
|
Sign up to set email alerts
|

Cementum‐like tissue deposition on the resorbed enamel surface of human deciduous teeth prior to shedding

Abstract: Prior to the shedding of human deciduous teeth, odontoclastic resorption takes place at the pulpal surface of the coronal dentin, and this resorption occasionally extends coronally from the dentinoenamel junction into the enamel. After the end of resorption, however, the resorbed enamel surface is repaired by the deposition of a cementum-like tissue. Using this phenomenon as an observation model, in this study we examined the sequence of cellular and extracellular/matrix events involved in the enamel resorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The increase of cellular influx could be accelerating the phenomenon, causing anoikia and apoptosis of pulp cells (eg, odontoblasts), and, moreover, it could be promoting the release of cytokines acting in the activating stem cells (29,30). The latter are the cells responsible for the intermittency of resorption by differentiating and producing a mineralized tissue similar to the cement in the root and coronal dentin (14,17). In deciduous teeth, the cement-like tissue is responsible for the fixed/mobile variation of the tooth during physiological resorption (15).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The increase of cellular influx could be accelerating the phenomenon, causing anoikia and apoptosis of pulp cells (eg, odontoblasts), and, moreover, it could be promoting the release of cytokines acting in the activating stem cells (29,30). The latter are the cells responsible for the intermittency of resorption by differentiating and producing a mineralized tissue similar to the cement in the root and coronal dentin (14,17). In deciduous teeth, the cement-like tissue is responsible for the fixed/mobile variation of the tooth during physiological resorption (15).…”
Section: Discussionmentioning
confidence: 98%
“…Morphological changes occurring in the pulp tissue during the phenomenon of physiological resorption of deciduous teeth have been previously described in the literature (14)(15)(16)(17)(18)(19)(20)(21)(22). This phenomenon, genetically programmed, starts from an environment that leads to the apoptosis of cementoblasts and, in sequence, promotes osteoclastogenesis (23).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…[2][3] The same phenomenon or resorption-formation coupling of (a bone-like tissue) cementum to enamel also occurs piecemeal during the later stages of resorption of human deciduous teeth. 4 However, with the ravages of caries, tooth wear and trauma, the need for some form of mechanical preparation often arises. Again, one would consider that this a relatively modern phenomenon, but recent work has shown that the first interventional dental procedures date back to between 7500-9000 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mononuclear cells were found adjacent to degenerating odontoclasts and resorbed enamel surface from which the odontoclasts had moved or detached in the transitional stage of shedding (Sahara et al, 2004). This might indicate completion of resorptive process in the radicular part under heavy forces.…”
mentioning
confidence: 96%